Mandiri FM Cilegon Radio Broadcasting Management Strategy in Attracting Listeners' Interest in The Nyenyore Program - Rico Fajar Baskoro; Media Sucahya (LONTAR: Jurnal Ilmu Komunikasi, 2023)
Nyenyore is one of the broadcast programs on Radio Mandiri FM Cilegon. This program provides musical entertainment and information about community activities in the afternoon. However, this program is relatively new, this makes it difficult for Radio Mandiri FM to get listeners due to the decreasing intensity of conventional radio listeners and other private radio broadcasting institutions that have long broadcast primetime programs. To overcome this, proper management of radio broadcasting is needed so that the jam program can be packaged properly. This study uses a post-positivist paradigm through a qualitative approach using the case study method, because it will explore the performance of human resources in broadcasting management. This study uses interview data collection techniques, observation and documentation. The results of this study indicate the stages of planning, organizing, directing and giving influence and supervision carried out by broadcasting management in managing the Nyenyore program.